Kvarner in the Early Iron Age of the northern Adriatic - Blečić Kavur Martina (Arheološki vestnik, 2021)
In the early Iron Age of the northern Adriatic and Istria, Kvarner also had a special place. Its role and importance in communications and the circulation of goods are indicated by older and more recent research. Although mainly protective archaeological research has been carried out in the previous two decades, in addition to individual finds, a large amount of new material has been collected, some of which was utterly unexpected. This article presents a brief overview of researchers and the state of research, then representative material culture and important recent finds that allow us to treat the Kvarner community in a new light, especially in more concrete connection with neighbouring, but also distant cultural communities from the Alps to the Adriatic and the Apennines to the Balkans.